Study of spray breakup and mixture in a gasoline direct injection engine by using simulation - Muzammil, Mohamad Alias (2013)
The project is to study the spray breakup and mixture in Gasoline Direct Injection (GDI) The spray breakup and fuel air mixture in the injector system really important to improve the fuel efficiency of Gasoline Direct Injection (GDI) Engine. Engine by using simulation. By using the ANSYS Design Modeler, the design of the injector with different inlet size and combustion chamber has been done. Then, by using Computational Fluid Dynamic (CFD), ANSYS Fluent the flow simulation has been run. The results extracted from the simulation are spray cone angle and penetration length. The simulation is done based on different size of nozzle which are 0.2, 0.3, 0.4 and 0.5 mm. While for another variable is injection pressure which are 3, 6, 10, 15 and 20 Mpa. From the result, the spray cone angle is decreasing as the pressure increase which means the spray cone angle is inversely proportional to the injection pressure. While for another results, the penetration length is directly proportional to the injection pressure. The penetration length is increase as the injection pressure is increase. But, as the nozzle diameterincrease with the same pressure, the penetration length is decreases.